Pharmaceutical applications and phytochemical profi le of Cinnamomum burmannii - Al-Dhubiab, Bandar E. (Pharmacognosy Reviews, 2012)
Extensive studies have been carried out in the last decade to assess the pharmaceutical potential and screen the phytochemical constituents of Cinnamomum burmannii. Databases such as PubMed (MEDLINE), Science Direct (Embase, Biobase, biosis), Scopus, Scifi nder, Google Scholar, Google Patent, Cochrane database, and web of science were searched using a defi ned search strategy. This plant is a member of the genus Cinnamomum and is traditionally used as a spice. Cinnamomum burmannii have been demonstrated to exhibit analgesic, antibacterial, anti-diabetic, anti-fungal, antioxidant, antirheumatic, anti-thrombotic, and anti-tumor activities. The chemical constituents are mostly cinnamyl alcohol, coumarin, cinnamic acid, cinnamaldehyde, anthocynin, and essential oils together with constituents of sugar, protein, crude fats, pectin, and others. This review presents an overview of the current status and knowledge on the traditional usage, the pharmaceutical, biological activities, and phytochemical constituents reported for C. burmannii.
Keywords: Antibacterial; antioxidant; Cinnamomum burmanni; essential oil; Lauraceae